Ensino superior na IECLB: uma primeira história - Iung, Silvio (2010)
The subject matter of this dissertation is higher education within IECLB (the Evangelical Church of Lutheran Confession in Brazil). The paper starts out by examining the origin of congregational education in Brazil and its structural organization alongside public education. The formation of the congregational education system is presented, which started with primary schools linked to local church congregations that were set up in response to the difficulties with the lack of schools found by German Lutheran immigrants upon their arrival to Brazil. After setting the context for the emergence of congregational higher education and the tradition of congregational basic education, the paper analyzes the discussions around the creation of colleges and higher education courses within the Synod Riograndense, one of the founding constituents of IECLB. Special emphasis is given to the unsuccessful attempt to offer courses at the time when many other Brazilian institutions working with higher education started their activity. This paper attempts to understand the reasons underlying these difficulties and examines the alternatives adopted. Finally, attention is given to the successful emergence of courses in the 1970s, but which took effect especially at the turn of the 21st century. Our studies reveal that the option not to offer higher education stemmed from a larger context of the church that was then undergoing reorganization. Some internal uncertainty about who would bear the responsibility for offering courses further delayed the process. The paper concludes by indicating alternatives for higher education in IECLB to play a greater role in the context of Brazilian education. The research points out the need for a systematic review of the way colleges and courses are maintained by institutions within IECLB should they want to consolidate their position in Brazil.